2022
DOI: 10.1007/s12663-022-01710-9
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Oral Potentially Malignant Disorders: A Review on Prospective Screening Methods with Regard to Global Challenges

Abstract: Oral cancer is a cancer type that is widely prevalent in low-and middle-income countries with a high mortality rate, and poor quality of life for patients after treatment. Early treatment of cancer increases patient survival, improves quality of life and results in less morbidity and a better prognosis. To reach this goal, early detection of malignancies using technologies that can be used in remote and low resource areas is desirable. Such technologies should be affordable, accurate, and easy to use and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…As dental hygienists (DHs) and dentists (Ds) regularly see their patients, they should be able to identify patients at increased risk. After being referred to a specialist these patients could be enrolled in a follow‐up program at the primary point of care 33 . In difference to a previous study, 34 focusing on evaluating the level of comfort in clinicians for using different adjunctive screening devices, including brush biopsies, this study was the first to investigate in depth the role for DHs in screening for premalignant oral lesions in the primary care settings.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As dental hygienists (DHs) and dentists (Ds) regularly see their patients, they should be able to identify patients at increased risk. After being referred to a specialist these patients could be enrolled in a follow‐up program at the primary point of care 33 . In difference to a previous study, 34 focusing on evaluating the level of comfort in clinicians for using different adjunctive screening devices, including brush biopsies, this study was the first to investigate in depth the role for DHs in screening for premalignant oral lesions in the primary care settings.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that a pipeline for nuclei classification and localization using deep learning can contribute to minimize the subjectivity of the human analysis and also support the detection of cancer at early stages 39 . Through integration of explainable AI techniques, enabling cytologists to interpret and support the AI system, it is possible to develop an interactive tool with which medical and dental expertise can offer the best possible diagnostics at minimal cost 38,40–41 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current methods used to assess at‐risk patients are either invasive and too costly for larger initiatives or insufficiently sensitive and specific. To address this problem, intensive research is being conducted to find non‐invasive methods that can identify the risk of developing OSCC without requiring expensive equipment or expertise, allowing them to be handled at the point of care 6 …”
Section: Introductionmentioning
confidence: 99%